Purification, molecular cloning, and functional expression of the cholecystokinin receptor from rat pancreas. - Wank, S A (1992)
The cholecystokinin (CCK) family of peptides and their receptors are widely distributed throughout the gastrointestinal and central nervous systems where they regulate secretion, motility, growth, anxiety, and satiety. The CCK receptors can be subdivided into at least two subtypes, CCKA and CCKB on the basis of pharmacological studies. We report here the purification of the CCKA receptor to homogeneity from rat pancreas by using ion-exchange and multiple affinity chromatographic separations. This allowed partial peptide sequencing after chemical/enzymatic cleavage and synthesis of degenerate oligonucleotide primers. These primers were used for initial cloning of the cDNA from rat pancreas by PCR. The predicted protein sequence of the cDNA clone contained the five partial peptide sequences obtained from the purified protein. Seven putative transmembrane domains suggest its membership in the guanine nucleotide-binding regulatory protein-coupled receptor superfamily. In vitro transcripts of the cDNA clone were functionally expressed in Xenopus oocytes and displayed the expected agonist and antagonist specificity.